From folklore to dance: Global expansion and potential of K-dance through cultural content “Dokkaebi (Goblin)” - Chang, So-Jung (Edelweiss Applied Science and Technology, 2025)
Korea's traditional culture and the folklore element "Dokkaebi" have long inspired creativity with their historical depth and imaginative appeal, serving as a basis for various cultural and artistic content. This study aims to apply the Theory of Possible Worlds to "Dokkaebi," transforming it into a new form of K-dance and exploring its potential for global expansion. By reinterpreting "Dokkaebi" as a creative and modern cultural content, the research seeks to highlight the diversity and creativity of Korean culture on the global stage. The study focuses on three key objectives. First, it utilizes the Theory of Possible Worlds to analyze "Dokkaebi," expanding the boundaries of culture and knowledge. Second, it creates innovative K-dance movements inspired by traditional folklore, thereby diversifying the genres within the Korean Wave (Hallyu). Third, it explores creative storytelling and choreography, extending beyond conventional methods to develop performances suitable for global audiences. This research is expected to serve as foundational material for the development of K-dance and the broader cultural content industry.